PENGARUH PENERAPAN MODEL KOOPERATIF TIPE THINK TALK WRITE TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS XI IPA SMAN 1 SUNGAI BEREMAS KABUPATEN PASAMAN BARAT - Fitriani, Arnes; Zulfaneti, Zulfaneti; Haryono, Yulia (STKIP PGRI Sumbar, 2013)
The research was background by the understanding of mathematical concept achieved class XI IPASMAN 1 Sungai Beremas Pasaman Barat is still low. This is because the less students construct own knowledge gained from the result of the discussion.Thisresearch purposes to find out if the students mathematical understanding the applying cooperative learning types think talk write better than on a mathematical concept understanding students with conventional learning on student in grade XI IPASMAN 1 Sungai Beremas Pasaman Barat. This is the kind of research experiments. The population in this study are all grade XI IPA SMAN 1 Sungai Beremas Pasaman Barat years lesson 2012/2013. The technique of sampling was done randomly,SelectedÂ grade XI IPA.1 as experimental class and XI IPA.2 as the class of the control. The instrument which was used in this research was essay test with index of reliability = 0,85. Mathematical concept understanding test result student class experiments is 80,10and control class is 71,58. Hypothesis testing using the one way of t-test with the help of software MINITAB, obtained P- value of 0,018is smaller than Î± = 0,05. So it can be concluded the understanding of the mathematical concept of student using cooperative model types think talk write better than on understanding concept that apply to conventional learning at grade XI IPA SMAN 1 Sungai Beremas Pasaman Barat.